Cervical spine fragility fractures in older people: 5-year experience at a regional spine centre. (10th June 2020) - Tarawneh, Ahmad; Taqvi, Syed; Salem, Khalid; Sahota, Opinder
Abstract: Background: cervical spine fractures are particularly prevalent in older people and commonly occur following a fall from standing height or less. Atlanto-axial complex (AAC) and, particularly, odontoid process (OP) fractures are the most prevalent injuries. Objective: to investigate the incidence and characteristics of cervical spine fractures in older patients presenting to a regional spine centre. Methods: a retrospective review of the clinical records and imaging of all patients aged 70 years and over presenting to a regional spinal unit with a cervical injury over a 5-year period was performed. Patient demographics, mechanism of injury, level of fracture, stability of the fracture, treatment modality, imaging modality and mortality rates were collected and analysed. Results: during the period between 2015 and 2019, a total of 209 patients aged 70 years and over were presented to the regional spine unit. The mean age at presentation was 82.4 (±7.5) years. Low-energy trauma was the commonest mechanism of injury ( n  = 169; 80.9%). MRI was undertaken in a quarter of the patients. One-hundred and fifty-one patients (72.2%) suffered an AAC Injury with OP fractures forming the majority of this group ( n  = 119; 78.8%). One-hundred and ninety-nine patients were treated conservatively, and the overall 30-day mortality rate was 8.1%. Conclusion: cervical spine fractures are not uncommon amongst older people and are mostly the result of low-energy trauma and predominantly affect the axial cervical spine. The majority of these injuries are managed conservatively with an orthosis. The fractures nevertheless are a serious injury, with a high mortality rate at 30 days.